Fecal Sludge Management in Developing Countries: Developing Countries Comparison - Nadia Paramita; Raldi Hendrotoro Seputro Koestoer (Universitas Diponegoro, 2021)
Several factors that influence the achievement of the sustainability of an MSS management system are identified. This study aims to determine what aspects of sustainability affect a system's municipal wastewater sludge management to run appropriately using conventional technology. The method used in this research is a comparative approach. The study compares urban domestic wastewater focusing on fecal sludge management (FSM) in Egypt and Indonesia. It is known that the sustainability factor of wastewater management systems includes economic, social, environmental, and technological factors. In Indonesia, institutional, which is also included in the social aspect, becomes the most significant limitation to implement the appropriate FSM. The best technology chosen for Egypt is anaerobic digestion, while in Indonesia, the right technology chosen is sludge drying bed (SDB) and also the combination of solid separation chamber (SSC) with draining area (DA). From an economic point of view, the 2 sub-factors that influence the sustainability system are investment cost and operation and maintenance cost. Regarding socio-culture, the awareness and participation of the community and the private sector needs to be increased to achieve the sustainability of sludge management services in both countries